2016
DOI: 10.1007/s11814-015-0215-7
|View full text |Cite
|
Sign up to set email alerts
|

Economical synthesis of complex silicon fertilizer by unique technology using loess

Abstract: Loess processed material (LPM) was produced as a substitute for silicon, clay and minerals, and applied to tomato and cucumber cultivation. LPM was produced by using a NaOH addition ratio of 30%, a reaction temperature of 1,200 o C, a reaction time of 1 h, and an alumina ball diameter of 10 mm. Treatment with a 200-fold diluted LPM solution resulted in respective increase of 7.8% and 8.3% in the weight and quantity of the tomato fruit, and a 31.7% increase in the quantity of cucumber fruit produced, when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This process improves the solubility of SiO 2 in a colloidal form, as confirmed by an analysis using an inductively coupled plasma-optical emission spectrometer (DV3300, Perkin Elmer, USA). The resulting material was ground to 20-50 µm according to Jung et al (2014) and Yoon et al (2016). The chemical composition of PRC consisted of SiO 2 (31.1%), Na 2 O (25.6%), Al 2 O 3 (19.0%), Fe 2 O 3 (7.47%), K 2 O (1.30%), CaO (0.95%), TiO 2 (0.94%), MgO (0.73%), and other materials (13.91%).…”
Section: Materials and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This process improves the solubility of SiO 2 in a colloidal form, as confirmed by an analysis using an inductively coupled plasma-optical emission spectrometer (DV3300, Perkin Elmer, USA). The resulting material was ground to 20-50 µm according to Jung et al (2014) and Yoon et al (2016). The chemical composition of PRC consisted of SiO 2 (31.1%), Na 2 O (25.6%), Al 2 O 3 (19.0%), Fe 2 O 3 (7.47%), K 2 O (1.30%), CaO (0.95%), TiO 2 (0.94%), MgO (0.73%), and other materials (13.91%).…”
Section: Materials and Experimental Designmentioning
confidence: 99%
“…The agricultural field has reported red clay availability (Kim et al, 2014); however, the prominent components that constitute red clay are insoluble and exhibit limited absorption in soil and plants, even when used as a powder (Seo et al, 2014a). Fortunately, processed red clay (PRC; Patent #0886082, Republic of Korea) is designed to remove impurities and enhance mineral bioavailability and to improve soil fertility and microbial activity (Jung et al, 2014;Yoon et al, 2016). Biofertilization utilizes plant and animal wastes to enrich soil with organic matter and nutrients, employing microorganisms to metabolize these by-products for enhanced absorption by plant roots (Montesdeoca-Flores et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, more improvement is necessary to make it practical. Yoon et al [10] reported economical synthesis of complex silicon fertilizers using loess with loess processed materials (LPM). LPM was produced by adding 30% NaOH at 12008C for 1 h. Treatment with a 200-fold diluted LPM solution resulted in increases of 7.8 and 8.3% in the weight and quantity of tomatoes, respectively, and 31.7% in the quantity of cucumbers.…”
Section: Introductionmentioning
confidence: 99%